The Influence of Current Ratio (CR), Debt To Equity Ratio (DER), Net Profit Margin (NPM), and Firm Size on Stock Returns with Dividend Payout Ratio (DPR) as an Intervening Variable - Pustika, Titin Hestri (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
The aim of this research is to test and analyze the influence of Current Ratio (CR), Debt To Equity Ratio (DER), Net Profit Margin (NPM), and Firm Size on Stock Returns with Dividend Payout Ratio (DPR) as an intervening variable. This research uses causal research (cause and effect). The analytical technique for processing and analyzing data uses Eviews 12 software with multiple linear regression testing and the Sobel test. The results of this research show that in structural I, the Debt to Equity Ratio (DER) and Net Profit Margin (NPM) partially have a positive influence on the Dividend Payout Ratio (DPR). Meanwhile, the Current Ratio (CR) and Firm Size variables partially have no influence on the Dividend Payout Ratio (DPR). Structural II states that the Net Profit Margin (NPM) variable partially has a positive effect on Stock Returns, while the Current Ratio (CR), Debt to Equity Ratio (DER), Firm Size, and Dividend Payout Ratio (DPR) variables partially have no effect. on Stock Returns. The Sobel Test results explain that the Dividend Payout Ratio (DPR) variable is unable to mediate or intervene in the influence of Current Ratio (CR), Debt to Equity Ratio (DER), Net Profit Margin (NPM), and Firm Size on Stock Returns.